'Every single student counts': leadership of professional development underpinned by social justice for sessional staff in a South Australian university. Issue 1 (1st January 2021) - Hattam, Sarah K; Weiler, Tanya
ABSTRACT: This paper reports on continuing professional development (CPD) innovations in an Australian university to address challenges commonly faced by sessional academics teaching progressively diverse student cohorts. With the impact of Widening Participation (WP) policy increasing university participation of students in recognised equity groups, equipping educators with structured CPD highlighting the strengths of pedagogies underpinned by social justice is essential. Through interviews with teaching staff, our study examines the impact of CPD in our enabling programme at the University of South Australia. This paper outlines how the development and implementation of CPD initiatives focused on social justice have increased educator confidence to engage with and support students from under-represented groups. Our paper demonstrates leadership of these initiatives has both led to the coordination of this approach to CPD and the development of a Community of Practice (CoP). We have built a CoP dedicated to developing social justice leaders in classrooms, positively contributing to changing the hegemonic approaches commonly found in teaching in higher education (HE) due to the increasing influence of neo-liberalism on both universities and educators.